PVP Treatment Induced Gradient Oxygen Doping in In2S3 Nanosheet to Boost Solar Water Oxidation of WO3 Nanoarray Photoanode. Issue 18 (23rd March 2020) - Tian, Wei; Chen, Cheng; Meng, Linxing; Xu, Weiwei; Cao, Fengren; Li, Liang
Abstract: The photoelectrochemical performance of the WO3 photoanode is limited by the severe charge recombination in the bulk phase and at the WO3 /electrolyte interface. Herein, In2 S3 nanosheets are integrated onto the surface of the WO3 nanowall array photoanode, followed by a facile polyvinylpyrrolidone (PVP) solution treatment. The PVP treatment results in sulfur vacancies and a gradient oxygen doping into In2 S3 from surface to interior, which induces the formation of a gradient energy band distribution. The gradient band structured In2 S3 and type II band alignment at the WO3 /In2 S3 interface simultaneously create a channel that favors photogenerated electrons to migrate from the surface to the conductive substrate, thereby suppressing bulk carrier recombination. Meanwhile, the sulfur vacancies and oxygen doping contribute to increased charge carrier concentration, prolonged carrier lifetime, more active sites, and small interfacial transfer impedance. As a consequence, the PVP treated WO3 /In2 S3 heterostructure photoanode exhibits a significantly enhanced photocurrent of 1.61 mA cm −2 at 1.23 V versus reversible hydrogen electrode (RHE) and negative onset potential of 0.02 V versus RHE. Abstract : A facile polyvinylpyrrolidone solution treatment of a WO3 /In2 S3 heterostructure induces gradient oxygen doping and sulfur vacancies into In2 S3, which enhance carrier density, prolong carrier lifetime, and increase surface active sites. The oxygen doping triggered gradient band structure in In2 S3 promotes the carrier transfer and separation. These synergistic effects greatly boost the photoelectrochemical performance of WO3 /In2 S3 photoanodes.